Experimental investigation of supercritical fluid heat transfer properties in a miniature heat sink / Ameer Abed Jaddoa - Jaddoa, Ameer Abed (Universiti Teknologi MARA, 2022)
Currently, efficient heat transmission for compact electronic elements is an essential matter. The objective of this project is to build a test rig to study the heat transfer effect of SCF-CO2 on the miniature heat sink, which is used in cooling in much small electronic equipment. It needs a heat sink with a liquid cooling scheme that meets these demands as much as feasible. The dimensions of 20 mm x 20 mm and a width of 3 mm were adopted for features of heat transfer as well as the fluid flow of supercritical CO2 in heat sink copper 360 alloys in this study. A heat sink has 20 homogeneous arrays of fins and 19 tubes, each having a rectangular cross-section and a 1mm hydraulic diameter. Moreover, the adopted pressures, temperatures, and mass velocity ranges were 7.5 to 12 MPa, 35 to 50 oC, and 100 to 500 Kg m-2 s-1, respectively, wherein the CO2 cooled under these conditions. The results of the experiment found that there is a substantial impact on the properties of liquid inflow and temperature motion by the system pressure, the temperature of CO2 as well as cluster velocity. Additionally, as the medium temperature of CO2 in the adjacent significant point area increased, the pressure decreased and the medium temperature movement factor augmented dramatically. It was also noted that the medium temperature movement factor peaked at the pseudo-critical temperature. Using the obtained data, a novel correlation mechanism for limited convection of super-critical CO2 in regular multi-port micro tubes based on chilling conditions was constructed using the obtained coefficients in this study.